Exploring FPGA Acceleration for Distributed Serverless Computing - Yang, Ziyi; Fahmy, Suhaib A. (International Conference on Field-programmable Logic and Applications, 2023)
Serverless computing has become a popular cloud computing paradigm. However, its deployment abstraction entails significant performance overheads. We explore the potential for enabling serverless computing on FPGAs and present some early results that show the concurrency and scalability benefits on a stream processing workload. The FPGA enables flows of network data to flow directly into accelerators, which is beneficial for scenarios involving large packets and multiple request streams.